Protection of civilians - Willmot, Haidi; Mamiya, Ralph; Sheeran, Scott (Law teacher); Weller, M. (Marc) (Oxford : Oxford University Press, 2016)
The protection of civilians is a highly topical issue at the forefront of international discourse, and has taken a prominent role in many international deployments. It has been at the centre of debates on the NATO intervention in Libya, UN deployments in Darfur, South Sudan, and the Democratic Republic of the Congo, and on the failures of the international community in Sri Lanka and Syria. Variously described as a moral responsibility, a legal obligation, amandated peacekeeping task, and the culmination of humanitarian activity, it has become a high-profile concern of governments, international organisations, and civil society, and a central issue in international peace and security. This book offers a multidisciplinary treatment of this important topic, harnessing perspectives from international law and international relations, traversing academia and practice.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 2, 2016).
Keywords: Humanitarian law; War -- Protection of civilians; Law; International law